ESMO guidelines consensus conference on malignant lymphoma 2011 part 1: diffuse large B-cell lymphoma (DLBCL), follicular lymphoma (FL) and chronic lymphocytic leukemia (CLL) - Ghielmini, Michele; Vitolo, U.; Kimby, E.; Montoto, S.; Walewski, J.; Pfreundschuh, M.; Federico, M.; Hoskin, P.; McNamara, C.; Caligaris-Cappio, F.; Stilgenbauer, S.; Marcus, R.; et al. (Annals of oncology, 2013)
To complete the existing treatment guidelines for all tumor types, ESMO organizes consensus conferences to better clarify open issues in each disease. In this setting, a consensus conference on the management of lymphoma was held on 18 June 2011 in Lugano, immediately after the end of the 11th International Conference on Malignant Lymphoma. The consensus conference convened ∼45 experts from all around Europe and selected six lymphoma entities to be addressed; for each of them three to five open questions were to be discussed by the experts. For each question, a recommendation should be given by the panel, supported by the strength of the recommendation based on the level of evidence. This consensus report focuses on the three most common lymphoproliferative malignancies: diffuse large B-cell lymphoma, follicular lymphoma and chronic lymphocytic leukemia. A second report will concentrate on mantle cell lymphoma, marginal zone lymphoma and T-cell lymphomas.
Gesehen am 04.02.2020
First published: 21 November 2012